SIKAP MAHASISWA TINGKAT TIGA PROGRAM DIPLOMA III KEPERAWATAN UNIVERSITAS MUHAMMADIYAH MALANG TENTANG PENGGUNAAN UNIVERSAL PRECAUTION (ALAT PERLINDUNGAN DIRI) - Susanti, Henny Dwi (Universitas Muhammadiyah Malang, 2009)
Universal Precaution is one of way for decrease of infection with assumes that all contiguity directly with fluid of body and blood contain spreading of Universal Precaution used. This function to push trans microorganisms cause infection between patient with other, patient with medic, and medic with patient .some of way to push the spreading decease risk is Universal Precaution used. Goal of the research are to know attitude of students in nursing academy about Universal Precaution used. The research design is using descriptive analytic. Descriptive design is research for to know variable value with one variable or independent without make ratio or connecting with the other variables. Result of research that parts of respondent have favorable attitude (58 %) and almost a half (42 %) respondent have unfavorable attitude about Universal Precaution used. Researcher give suggestion to student of nursing academy for increasing knowledge about Universal Precaution used with reading or getting information via audio visual or mass media so the attitude so the attitude of student about Universal Precaution used maximal. Â Key Words: The attitude of students, Universal Precaution used